Accelerated consolidation of reconstituted dredged marine soils with drainage control - S.M Johan, Siti Farhanah (2021)
Dredging is a process of removal and transportation the underwater sediments from one place to another in order to deepen the sea vessels for harbour structure. The dredging sediments called as dredged marine soils (DMS). DMS are generally known as a geo-waste as they are poor quality soils which are relatively weak in strength, high in compressibility and in low permeability. In Malaysia, DMS are normally disposed and currently not recycled. This research is focused on the accelerated consolidation rate with the drainage control for potential reuse of the material as backfill in the reclamation works. Industrial by-products of granular form were adopted as drainage media, including recycled pavement materials (RPM) and palm oil clinker (POC). Sand was included as control material in this research. Standard and modified-large oedometer tests were conducted to investigate efficacy of the granular by-products as drainage media for improved consolidation rate of DMS. The DMS sample had high water content of 218% and was classified as high plasticity clay. The chemical composition showed rather high contents of natrium oxide, silica oxide and aluminium oxide, while POC and RPM contained predominantly silica oxide. The proportioned samples of 50% and 100% of granular materials per sample height were incorporated in the oedometer test with different drainage configurations (single, double and radial). The end of primary consolidation time monitoring showed that the 100% thickness of drainage layer for all the granular materials shortened the consolidation time varied by 9% to 29% compared to 50% thickness of drainage layer. The presence of granular materials as drainage layer to the DMS facilitated a faster process of pore water dissipation and have higher value of coefficient of consolidation (Cv) that varied with 1.3 – 5.7 m 2 /yr. Significantly, thickness of granular drainage influenced the volume of compressibility (mv) and Cv. The results of the research suggest that drainage granular layer could be useful in practice to accelerate the consolidation of DMS for the future construction project i.e. land reclamation.